Urban household food insecurity and pediatric malnutrition: evidence from the Divina Providencia Hospital in Luanda, Angola - Carbone, Andrea Scimone; Roscioli, Federico; Mazziotta, Matteo (Frontiers in Public Health, 2025)
IntroductionFood insecurity and poverty mechanisms often intertwine, negatively affecting the well-being of families and children, particularly those with acute malnutrition. In urban Angola, limited evidence exists on how socioeconomic deprivations influence household food security and treatment outcomes for malnourished children. Drawing on the Amartya Sen Capability Approach, this study investigates the determinants of household food consumption, weight gain during hospitalization, and outpatient treatment duration among children with acute malnutrition.MethodsWe combined analyses from an original household survey of 84 families with hospital records from 1,259 children admitted to the Divina Providencia Hospital in Luanda between January 2019 and June 2021. Data included socioeconomic indicators, anthropometric measurements at admission and discharge, and treatment duration. Classification and Regression Trees (CART) were applied to identify key socioeconomic and clinical predictors across multiple dependent variables.ResultsLower household food consumption was observed when families could not afford at least 2.5 meals per day, had a monthly income below 30,000 Kwanzas, and when the mother’s education was less than 9.5 years. Anthropometric indicators at admission significantly influenced children’s ability to gain weight during hospitalization. Poverty and food insecurity were associated with longer outpatient treatment durations.DiscussionThe findings highlight the effects of socioeconomic deprivations on food insecurity and recovery from acute malnutrition in children. Targeted interventions addressing low income, inadequate maternal education, and poor dietary access are essential to break the cycle of intergenerational poverty and malnutrition. Stronger policy implementation and integration of social protection with nutrition services are recommended to improve child health outcomes in peri-urban settings.